(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2022)
The purpose of this study was to examine the effects that time and community assistance (in the form of donations) had on accrued recoveries from the Novel Coronavirus. This study examined donation transaction data from a community-based national virtual donation platform in conjunction with government released figures on populations and COVID-19 cases in the Philippines. Findings from a Generalized Linear Model showed that at a 0.001 level of significance, the passage of time affected accrued recoveries by about 14 (13.23) daily, while cumulative individual donations improved recoveries by about 2 (1.69) people. A series of simulations that visualized the effects of time and donations on recoveries evidenced that accrued recoveries were accelerated by donations. Results from the analysis generated a series of recommendations based on Resource-Advantage Theory, along with Disaster Management Theory as applied to supply-chains. The first recommendation was to allow broader access to the platform as an information exchange. An expansion of the crowdsourcing features on the platform was a second recommendation. A third recommendation was establishing a relief distribution network prior to the next disaster.